Sejarah Kemunduran Umat Islam - Mukhlis Rahmanto (LITERASI (Jurnal Ilmu Pendidikan), 2009)
Answering the question of why Muslims fall down suffering in many fields, including economics, is the work done by Chapra in this book. By using the model of the dynamics of socio-economic  analysis  of  Ibn Khaldun,  he  began  to  read  and  trace the history of Muslims.  Eventually he gained a few main factors causing the decline of Islam, namely:  the movement of sufism which is not running on rails of origin,  poor appreciation of the  role of women, and declining quality of education. Deterioration occurs because of political authority (G)  negligent of  its responsibilities,  especially  in  upholding justice  and  Shariah,   guarantee facilities to the people (N),   and realize their full potential. According to him,  an urgent solutions must be implemented by Muslims are  moving  revival (resurrection) of Islam with one of  its programs to critically analyze what is coming from the West to conform to the Islamic world view and values.  The call to develop Islamic economics is just one strand of the Islamic revivalism movement.Keywords: socio-economic dynamics, Sufism, women, education, despotism, revivalism